Fireballs on Mars and Earth, impact process and seismic effects - Neidhart, Tanja (Curtin University, 2022)
This work investigated new crater clusters on Mars that form when the impactor breaks up in the atmosphere. Bulk search for seismic signals from fireballs on Earth was made, to compare outcomes between Earth and Mars. Results from this study are relevant for understanding impact events on Mars and respective seismic data recorded by the NASA's InSight mission currently operating on Mars.